2010
DOI: 10.1007/s00284-010-9611-8
|View full text |Cite
|
Sign up to set email alerts
|

New Insights in Trichoderma harzianum Antagonism of Fungal Plant Pathogens by Secreted Protein Analysis

Abstract: Trichoderma harzianum ALL42 were capable of overgrowing and degrading Rhizoctonia solani and Macrophomina phaseolina mycelia, coiling around the hyphae with formation of apressoria and hook-like structures. Hyphae of T. harzianum ALL42 did not show any coiling around Fusarium sp. hyphae suggesting that mycoparasitism may be different among the plant pathogens. In this study, a secretome analysis was used to identify some extracellular proteins secreted by T. harzianum ALL42 after growth on cell wall of M. phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 33 publications
5
56
0
2
Order By: Relevance
“…Analogous findings have been reported against S. rolfsii using T. harzianum in 2001 [38]. It was reported that S. rolfsii and mycelia of other fungus were inhibited by T. harzianum ALL42 strain which found to overgrow in Petri plate in dual culture method [39]. It also forms coiling around hyphae resulting in generation of appressoria.…”
Section: Discussionsupporting
confidence: 78%
“…Analogous findings have been reported against S. rolfsii using T. harzianum in 2001 [38]. It was reported that S. rolfsii and mycelia of other fungus were inhibited by T. harzianum ALL42 strain which found to overgrow in Petri plate in dual culture method [39]. It also forms coiling around hyphae resulting in generation of appressoria.…”
Section: Discussionsupporting
confidence: 78%
“…This fungus releases cell wall-degrading enzymes, which combat plant pathogens through a variety of mechanisms (Ghisalbert and Sivasithamparam, 1991;Monte, 2001;Monteiro et al, 2010). However, T. harzianum T S1 has a long culture period and high production costs, which have restricted T. harzianum T S1 production levels (da Silva et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of studies have identified enzymes and effectors involved in host recognition and the mycoparasitic responses of Trichoderma (40,46,51); however, their modes of action and the mechanisms determining host specificity remain poorly understood. Mainly expressed-sequencetag (EST) libraries of different Trichoderma strains obtained under various growth conditions have contributed significantly to the large-scale identification of active genes (63,64).…”
mentioning
confidence: 99%